Right to Ride : Streetcar Boycotts and African American Citizenship in the Era of Plessy v. Ferguson - Kelley, Blair Murphy, 1973- (Book collections on Project MUSE., 2010)
Focusing on three key cities--New Orleans, Richmond, and Savannah--Kelley explores African Americans' organized efforts to resist the passage of segregation laws dividing trains and streetcars by race in the early Jim Crow era. The book forces a reassessment of the timelines of the black freedom struggle, revealing that a period once dismissed as the age of accommodation should in fact be characterized as part of a history of protest and resistance.